2015
DOI: 10.5897/jgrp2015.0498
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals concentration in soil and Amaranthus retroflexus grown on irrigated farmlands in the Makera Area, Kaduna, Nigeria

Abstract: This study was conducted to determine the heavy metals concentration in soil andFurthermore, the study revealed that some areas of the sample site were more polluted by a particular metal than the other due to the prevailing anthropogenic activities in the area, and that all areas of the site run the risk of pollution by Cd, Cr and Fe in vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 5 publications
5
17
10
Order By: Relevance
“…The violation of the maximum permissible limits of Pb set by the WHO, EU, and US EPA is a cause for public health concern considering the frequency of exposure. The Pb concentration range for the pepper fruit samples in this study is lower than that reported for ginger (22 mg/kg) and in Negro pepper (5 mg/kg) in a study on the heavy metal content of spices in Abuja, Nigeria [23], that reported for leafy vegetables from Kaduna state Nigeria [24] and that reported for beans samples from Italy, Mexico, India, Japan, Ghana and Ivory Coast with a Pb concentration range of 4.084-14.475ppm [25] and homegrown vegetables near a former chemical manufacturing facility in Tarnaveni, Romania [26]. But the results are higher than the values reported for the concentration of Pb in cereals from Kano and Kaduna states, Nigeria [27,28].…”
Section: Resultscontrasting
confidence: 69%
“…The violation of the maximum permissible limits of Pb set by the WHO, EU, and US EPA is a cause for public health concern considering the frequency of exposure. The Pb concentration range for the pepper fruit samples in this study is lower than that reported for ginger (22 mg/kg) and in Negro pepper (5 mg/kg) in a study on the heavy metal content of spices in Abuja, Nigeria [23], that reported for leafy vegetables from Kaduna state Nigeria [24] and that reported for beans samples from Italy, Mexico, India, Japan, Ghana and Ivory Coast with a Pb concentration range of 4.084-14.475ppm [25] and homegrown vegetables near a former chemical manufacturing facility in Tarnaveni, Romania [26]. But the results are higher than the values reported for the concentration of Pb in cereals from Kano and Kaduna states, Nigeria [27,28].…”
Section: Resultscontrasting
confidence: 69%
“…But the results are higher than that reported for the concentration of Pb in cereals from Kano and Kaduna states, Nigeria [29,30]. The value was still higher than the range (0.116 to 0.390) reported by Ahmed and Mohammed in Egypt [31] in 2005 and the range (0.007 to 0.032 mg/kg) reported by Okoye et al [32] in a study conducted in South east of Nigeria in 2009 The Pb concentration range for the leaf samples in this study is lower than that reported for leafy vegetables from Kaduna state Nigeria [33] and that reported for beans samples from Italy, Mexico, India, Japan, Ghana and Ivory Coast with a Pb concentration range of 4.084-14.475 ppm [34] and the Pb result for homegrown vegetables near a former chemical manufacturing facility in Tarnaveni and Romania [35]. The concentration of Cd (mg/kg) range from 0.042 to 0.059 in the leaf samples, these values were higher than the range (0.002 to 0.004 mg/kg) reported by Edem et alin Wheat flours in 2009 [36].…”
Section: Discussioncontrasting
confidence: 70%
“…This value is very low when compared with the DPR standard of 36 mg/Kg. Also, in this study, the values were lower than those observed by Mohammed and Folorunsho (2015) in samples within Kaduna metropolitan city, Northern Nigeria. The low level of Zinc metal was not far fetch as there are relatively little activities that could influence the release of Zinc into the environment.…”
Section: Resultscontrasting
confidence: 87%